2013
DOI: 10.1002/ps.3637
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a nucleopolyhedrovirus isolate fromHelicoverpa armigeraas the basis for a biological insecticide

Abstract: The insecticidal properties of HearSNPV-SP1 mean that this strain is likely to prove useful as the basis for a biological insecticide for control of Helicoverpa armigera in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 42 publications
(89 reference statements)
2
35
0
1
Order By: Relevance
“…Moreover, additional genotypes may be present in the HearSP1-wt population, thus attenuating the influence of HearSP1B on HearSP1-wt transmissibility, as occurs with certain genotypic variants in wild-type isolates of SeMNPV (18) and Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV) (16). In contrast, among the different variants isolated from larvae that died during laboratory rearing, no marked differences in pathogenicity were detected, but differences in speed of kill were observed, with HearLB6 being among the fastest-killing variants, even more so than HearSP1-wt, which was previously selected as one of the fastest-killing isolates from diseased larvae collected in the Iberian Peninsula (36). These results are in line with data from previous studies performed with different variants of HearSNPV, in which variants of similar pathogenicities presented marked differences in speed of kill (36,50).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, additional genotypes may be present in the HearSP1-wt population, thus attenuating the influence of HearSP1B on HearSP1-wt transmissibility, as occurs with certain genotypic variants in wild-type isolates of SeMNPV (18) and Spodoptera frugiperda multiple nucleopolyhedrovirus (SfMNPV) (16). In contrast, among the different variants isolated from larvae that died during laboratory rearing, no marked differences in pathogenicity were detected, but differences in speed of kill were observed, with HearLB6 being among the fastest-killing variants, even more so than HearSP1-wt, which was previously selected as one of the fastest-killing isolates from diseased larvae collected in the Iberian Peninsula (36). These results are in line with data from previous studies performed with different variants of HearSNPV, in which variants of similar pathogenicities presented marked differences in speed of kill (36,50).…”
Section: Discussionmentioning
confidence: 99%
“…The HearSNPV-SP1 (HearSP1) isolate was originally obtained from diseased larvae from tomato crops in Guadajira, Badajoz, Spain. HearSP1 was included as a reference isolate in this study because it was previously identified as a highly pathogenic isolate in terms of concentration-mortality metrics (27,36). From a total of 17 HearSNPV isolates obtained from individual larvae that died of polyhedrosis disease during rearing of H. armigera larvae collected from cotton crops in Lebrija, Spain, six different EcoRI restriction endonuclease profiles were identified.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations